ATP / CCS / SA-PEI aerogel as well as preparation method and application thereof

By using aerogel adsorbents prepared by raw materials such as ATP, CCS, PEI and SA, the problem of complex and high cost of adsorbent raw materials in the prior art is solved, and efficient adsorption of dye pollutants and heavy metal ions is achieved, with good thermodynamic stability and reusability.

CN119549074APending Publication Date: 2025-03-04ANHUI POLYTECHNIC UNIV

Patent Information

Application Number
CN202411892194.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The adsorbent raw materials used in the prior art to remove dye pollutants and heavy metal ions are complex and have high costs, making it difficult to meet the needs of low cost and good adsorption effect.

Method used

Aerogel was prepared by ion cross-linking method by using concave and convex rod soil (ATP), carboxylated chitosan (CCS), polyethyleneimine (PEI) and sodium alginate (SA) as raw materials to form an adsorbent with high specific surface area and good porosity.

Benefits of technology

The prepared ATP/CCS/SA-PEI aerogels exhibit good adsorption performance, and the maximum adsorption amounts to the dye pollutants methylene blue, Congo red and heavy metal ion Cu(II) can reach 206 mg/g, 290.13 mg/g and 228.24 mg/g, respectively, with excellent thermodynamic stability and efficient adsorption efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549074A_ABST
    Figure CN119549074A_ABST
Patent Text Reader

Abstract

The invention provides ATP / CCS / SA-PEI aerogel as well as a preparation method and application thereof, attapulgite ATP, carboxylated chitosan CCS, polyethyleneimine PEI and sodium alginate SA are adopted as raw materials, and polymer modification and crosslinking are promoted through an ionic crosslinking method to form the aerogel. The preparation method comprises the following steps: firstly, adding a prepared CCS solution into an SA solution to obtain a CCS / SA solution; the preparation method comprises the following steps: adding a CCS solution into a reaction kettle, adding an ATP suspension, finally adding a PEI solution, uniformly mixing, pouring into a plastic mold, freeze-drying, cross-linking, washing with water, and freeze-drying again to obtain the ATP / CCS / SA-PEI aerogel. The aerogel prepared in the invention has the advantages of large specific surface area, many adsorption groups, good adsorption performance on dye pollutants and heavy metal ions, good thermal stability, reusability, and good application value in the removal of dye pollutants and heavy metal ions in sewage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation of adsorption materials, and specifically relates to an ATP / CCS / SA-PEI aerogel and a preparation method and application thereof, which are used for adsorption of dye pollutants and heavy metal ions. Background Art

[0002] Environmental pollution is becoming an increasingly serious problem. Due to chemical, industrial and agricultural activities, dye pollutants and heavy metal ion pollution have harmed the health of aquatic organisms, terrestrial organisms and humans. Therefore, it is an important task in the current field of environmental protection and public health to effectively treat wastewater containing dyes and heavy metals and reduce their negative impact on the environment and human health.

[0003] At present, the commonly used methods for removing dye pollutants and heavy metal ions are generally divided into chemical methods, biological methods, physical methods, etc. Specifically, they include precipitation method, oxidation method, electrochemical method, membrane separation method, flocculation method and adsorption method, etc. Among them, adsorption method has broad application prospects due to its advantages such as simple operation, low cost, short cycle, good selectivity and regenerable adsorbent.

[0004] The main factor and challenge of the adsorption process is the selection of suitable and efficient adsorbent.

[0005] The Chinese invention patent with the publication number CN 108439525 A published on August 24, 2018, discloses a sewage treatment agent for heavy metal pollution, and the disclosed raw materials include: polyethyleneimine, carbon disulfide, sodium hydroxide, starch xanthogenic acid, colloidal Bacillus, stone cassia powder, modified zeolite powder, modified bentonite, sodium alginate, humic acid, ferric chloride, nano titanium dioxide, cellulose, ferrous sulfate, photocatalyst, high-efficiency nickel removal agent, chitosan modified polymer flocculant, coagulant, dextran gel and deionized water. It effectively removes heavy metal ions in sewage through the dual coordination of adsorption and flocculation. However, its raw materials are complex and the cost is high.

[0006] Therefore, it is necessary to provide an adsorbent with low cost and good adsorption effect. Summary of the invention

[0007] The purpose of the present invention is to provide an ATP / CCS / SA-PEI aerogel and a preparation method thereof. Attapulgite (ATP), carboxylated chitosan (CCS), polyethyleneimine (PEI) and sodium alginate (SA) are selected as raw materials, and polymer modification and cross-linking are promoted to form aerogel through an ion cross-linking method. The prepared aerogel has a large specific surface area, good porosity, and many adsorption groups, and exhibits good adsorption performance for dye pollutants and heavy metal ions.

[0008] Another object of the present invention is to provide an application of ATP / CCS / SA-PEI aerogel for adsorption of dye pollutants and heavy metal ions, especially for adsorption of dye pollutants methylene blue (MB), Congo red (CR) and heavy metal ion Cu (II).

[0009] The specific technical solutions of the present invention are as follows:

[0010] A method for preparing ATP / CCS / SA-PEI aerogel comprises the following steps:

[0011] 1) adding carboxylated chitosan CCS solution dropwise to sodium alginate SA solution and stirring to obtain CCS / SA solution;

[0012] 2) adding the attapulgite ATP suspension to the CCS / SA solution, stirring, and then adding the polyethyleneimine PEI solution, stirring to form a mixed solution;

[0013] 3) pouring the mixed solution obtained in step 2) into a mold and freeze-drying it, soaking the obtained aerogel in a calcium chloride solution, then washing it with water; and then freeze-drying it to obtain ATP / CCS / SA-PEI aerogel.

[0014] In step 1), the solvent of the sodium alginate SA solution is water; the Mw of the sodium alginate SA used is 198.11 g / mol;

[0015] In step 1), the solvent of the carboxylated chitosan CCS solution is water; the carboxylated chitosan CCS used has CAS No. 9012-76-4, grade BR, and is water-soluble;

[0016] In step 1), the concentration of the carboxylated chitosan CCS solution is 6 wt %; the concentration of the sodium alginate SA solution is 3 wt %;

[0017] In step 1), the stirring refers to stirring the reaction at room temperature for 1 hour at a stirring rate of 1500 rpm.

[0018] In step 2), the solvents of the attapulgite ATP suspension and the polyethyleneimine PEI solution are both water; the concentration of the attapulgite ATP suspension is 2.5-10wt%, preferably 5wt%; the mass concentration of the polyethyleneimine PEI solution is 2.5-10wt%, preferably 7.5wt%;

[0019] The weight ratio of carboxylated chitosan CCS in carboxylated chitosan CCS solution, sodium alginate in sodium alginate SA solution, attapulgite in attapulgite ATP suspension, and polyethyleneimine in polyethyleneimine PEI solution is 1.2:0.6:0.5-2:0.25-1; the preferred mass ratio is: 1.2:0.6:1:0.75.

[0020] The polyethyleneimine PEI used had a Mw of 600 g / mol, 99%;

[0021] The attapulgite ATP used refers to attapulgite with a mesh size of 300 or more and prepared by spray granulation;

[0022] In step 2), the attapulgite ATP suspension is added to the CCS / SA solution, and the reaction time is stirred at room temperature for 2 hours;

[0023] Step 2) adding polyethyleneimine PEI solution and stirring to form a mixed solution for 0.5 hour.

[0024] Step 3) The concentration of the calcium chloride solution is 10wt%.

[0025] Step 3) freeze drying twice, both at -60°C for 48 hours.

[0026] The ATP / CCS / SA-PEI aerogel provided by the present invention is prepared by adopting the above method.

[0027] The present invention provides an application of ATP / CCS / SA-PEI aerogel, which can be used not only for adsorption of dye pollutants but also for adsorption of heavy metal ions, especially for adsorption of dye pollutants methylene blue (MB), Congo red (CR) and heavy metal ion Cu (II).

[0028] The inventors have found that by preparing an adsorbent with high porosity, high specific surface area and abundant functional group active adsorption sites, the adsorption effect can be improved. Chitosan, polyethyleneimine, sodium alginate and other polymer structures have abundant functional groups that can be used as adsorption sites. Therefore, by combining the advantages of functional group polymers and porous materials, aerogel porous materials are prepared to obtain an adsorbent with an adjustable skeleton, high surface area, good porosity and easy-to-operate mechanical structure. The present invention provides a method for preparing an aerogel containing a multifunctional base, wherein a clay material and a biomass material are mixed, and a cross-linking reaction is performed to obtain an aerogel containing a multifunctional base. The aerogel adsorbent has the characteristics of a rigid structure and a large specific surface area, which is conducive to separation and recycling, and maximizes the operability and practicality of the aerogel adsorbent containing a multifunctional base.

[0029] In the present invention, SA is a biodegradable natural polysaccharide material, which contains abundant carboxyl functional groups as controllable modification sites, ATP is an inorganic clay material, has a porous nanostructure, exhibits strong adsorption, and has strong cation exchangeability, CCS and PEI polymer surfaces have abundant amino and hydroxyl groups, which can be used as ion adsorption sites, and PEI is used as a nucleation site and an ion crosslinker to promote material modification and crosslinking to form aerogel. As an ion adsorbent, the aerogel can be adsorbed by chemical chelation between functional groups and ions, and can also be physically adsorbed by a porous structure, thereby exhibiting efficient ion adsorption performance. And the preparation method of the present invention is simple, and the aerogel ATP / CCS / SA-PEI has a uniform morphology and good thermodynamic stability, and can be recycled and reused after adsorption.

[0030] Compared with the prior art, the aerogel ATP / CCS / SA-PEI preparation method provided by the present invention is simple, the raw materials are simple, cheap and easy to obtain, the product post-processing is simple, and the composite gel has a large specific surface area and many adsorption groups. It shows good adsorption performance for dye pollutants methylene blue (MB), Congo red (CR) and heavy metal ions Cu (Ⅱ), and the maximum adsorption amount can reach 206mg / g, 290.13mg / g and 228.24mg / g respectively; it has excellent thermodynamic stability, high adsorption efficiency of dye pollutants and heavy metal ions, and can be recycled and reused after adsorption. It has good application value in the removal of dye pollutants and heavy metal ions in sewage. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The SEM images of ATP / CCS / SA and ATP / CCS / SA-PEI aerogels of Example 1; a1, a2 and a3: ATP / CCS / SA; b1, b2 and b3: ATP / CCS / SA-PEI;

[0032] Figure 2 TG curves of ATP, CCS, PEI, SA and ATP / CCS / SA-PEI aerogel before and after adsorption in Example 1;

[0033] Figure 3 The dynamic and static adsorption performance curves of the ATP / CCS / SA-PEI aerogel of Example 1 for Cu(Ⅱ), MB and CR;

[0034] Figure 4 The EDS test spectra of ATP / CCS / SA-PEI aerogel before and after adsorption in Example 1; a: before adsorption; b: adsorption of Cu(Ⅱ);

[0035] Figure 5The SEM images of the aerogels prepared in Comparative Examples 1 and 2, wherein a and b are SEM images of DE / CCS / SA-PEI; c and d are SEM images of MMT / CCS / SA-PEI;

[0036] Figure 6 Figure 1 is the adsorption curve of aerogels prepared in Example 1, Comparative Example 1 and Comparative Example 3; a is the adsorption curve of Cu(II) by DE / CCS / SA-PEI, MMT / CCS / SA-PEI and ATP / CCS / SA-PEI; b is the adsorption curve of MB by DE / CCS / SA-PEI, MMT / CCS / SA-PEI and ATP / CCS / SA-PEI; c is the adsorption curve of CR by DE / CCS / SA-PEI, MMT / CCS / SA-PEI and ATP / CCS / SA-PEI. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] In the present invention, attapulgite is referred to as ATP, carboxylated chitosan is referred to as CCS, polyethyleneimine is referred to as PEI, sodium alginate is referred to as SA, CCS (BR, water-soluble), PEI (Mw = 600 g / mol, 99%), SA (Mw = 198.11 g / mol). The attapulgite ATP used refers to attapulgite with a mesh size of 300 or more and prepared by spray granulation.

[0039] PEI in the examples was purchased from Shanghai Aladdin Chemical Reagent Co., Ltd., China, and ATP, CCS and SA were purchased from Sinopharm Chemical Reagent Co., Ltd. Other chemical reagents were purchased from common reagent platforms and used directly unless otherwise specified.

[0040] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0041] Example 1

[0042] A method for preparing ATP / CCS / SA-PEI aerogel comprises the following steps:

[0043] 1) First, 1.2 g CCS was dissolved in water to obtain a 6 wt% CCS solution; 0.6 g SA was dissolved in water to obtain a 3 wt% SA solution; 20 g CCS solution was added dropwise to 20 g SA solution, and the mixture was vigorously stirred at 1500 rpm for 1 h at room temperature to obtain a CCS / SA solution.

[0044] 2) directly weighing attapulgite powder, adding it to deionized water and stirring to obtain a suspension, then adding the obtained 20g 5wt% attapulgite ATP suspension to the above CCS / SA solution, stirring at room temperature at 500rpm for 2h to obtain a slurry ATP / CCS / SA mixture; then adding 10g 7.5wt% polyethyleneimine PEI solution, vigorously stirring at 1500rpm for 30min to form a mixed solution; wherein, the preparation method of 7.5wt% polyethyleneimine PEI solution is: adding 0.75g PEI to deionized water and stirring to obtain a 7.5wt% PEI solution.

[0045] 3) Pour the mixed solution obtained in step 2) into a plastic mold and freeze-dry at -60°C, with a vacuum degree of 2Pa, freeze-dry for 48 hours, and soak the obtained aerogel in a 10wt% calcium chloride solution for 4 hours to allow SA and CCS to react with Ca 2+ Fully cross-linked to form a stable network structure. Afterwards, thoroughly rinse with distilled water to remove incompletely cross-linked PEI and Ca 2+ The washed aerogel was then freeze-dried again at -60°C and a vacuum degree of 2 Pa for 48 h to obtain ATP / CCS / SA-PEI aerogel.

[0046] The preparation was carried out in the same manner as in Example 1, except that the concentration of the PEI solution and the concentration of the attapulgite ATP suspension were changed, and the specific amounts were shown in Table 1. In Table 1, serial numbers 1-5 are experiments in which the amounts of CCS, SA and PEI are fixed and only the concentration of the attapulgite ATP suspension is changed (the mass of the attapulgite ATP suspension is fixed), and serial numbers 6-10 in Table 1 are experiments in which the amounts of CCS, SA and ATP are fixed and only the concentration of the PEI solution is changed (the mass of the PEI solution is fixed).

[0047] The surface morphology of the aerogel prepared under the conditions of 1.2g CCS, 0.6g SA, 1g ATP, and 0.75g PEI was photographed by scanning transmission electron microscopy. Figure 1 SEM images of ATP / CCS / SA and ATP / CCS / SA-PEI aerogels of Example 1; a1, a2 and a3: ATP / CCS / SA; b1, b2 and b3: ATP / CCS / SA-PEI. Figure 1 a1, a2 and a3 show that the aerogel before adding PEI has more pores and a smoother surface. Figure 1 Figures b1, b2 and b3 show that after adding PEI, the structural surface of the aerogel becomes rough, the number of pores decreases, and the aggregation of particles becomes serious. This may be due to the addition of PEI, which leads to a higher cross-linking density and a weaker dispersion of other substances. However, this rough structure is conducive to the adsorption of pollutants.

[0048] The thermal stability of the raw materials and composite gel before and after adsorption was tested by TG thermogravimetric analyzer. Figure 2 As shown, the TG curves of ATP, CCS, PEI, SA and ATP / CCS / SA-PEI aerogels before and after adsorption of Example 1; the composite gel begins to decompose at about 50°C, which meets the operating temperature requirements of the adsorbent. The TG curve of the composite gel does not change much before and after adsorption, and has good thermal stability as an adsorbent.

[0049] Table 1. Ratio of ATP / CCS / SA-PEI aerogel raw materials

[0050]

[0051]

[0052] Example 2

[0053] An application of ATP / CCS / SA-PEI aerogel, specifically:

[0054] 1.255g CuSO4, 1g methylene blue (MB) and 1g Congo red (CR) were dissolved in deionized water to prepare 1000mg / L standard stock solutions of Cu(II), MB and CR, respectively. Subsequently, 5mL of the standard stock solutions of Cu(II), MB and CR were taken and transferred to a 100mL volumetric flask to prepare 50mg / L standard solutions of Cu(II), MB and CR. Different volumes of standard solutions (0.00, 1.00, 2.00, 3.00, 4.00, 5.00, 6.00mL) were added to 7 50mL volumetric flasks containing solutions with a concentration of 50mg / L. When constructing the standard curve of Cu(Ⅱ), 5mL EDTA-ammonium citrate solution and 5mL NH4Cl buffer solution were added in sequence, and the absorbance value was determined at a wavelength of 450nm using 1mL starch solution and 5mL copper reagent. For the standard curves of MB and CR, the absorbance was measured at wavelengths of 664 and 498nm, respectively.

[0055] The adsorption effect of aerogel on Cu(II), MB and CR is shown in the adsorption amount q e (mg·g -1 ) to evaluate, the adsorption amount q e The calculation formula is as follows:

[0056]

[0057] Where: C0, C e —The initial concentration of Cu(II), MB and CR solutions and the concentration at the time of adsorption equilibrium, mg·L -1 ;

[0058] m—mass of adsorbent, g;

[0059] V—Volume of Cr solution, mL.

[0060] In the initial adsorption experiment, 0.05 g of aerogel was accurately weighed and introduced into a 50 mL stoppered colorimetric tube containing Cu(II) (300 mg / L, pH = 4), MB (300 mg / L, pH = 6), and CR (300 mg / L, pH = 6) solutions. The colorimetric tube was sealed and the static and dynamic adsorption processes were carried out in a fume hood and shaker at ambient temperature. 1.00 mL of the solution was periodically poured into a 50 mL volumetric flask and diluted to volume with water for analysis. Subsequently, a buffer solution was introduced into the solution along with the color developer. The absorbance values ​​of Cu(II) ions were then measured at 450 nm, the absorbance values ​​of MB were measured at 664 nm, and the absorbance values ​​of CR were measured at 498 nm until equilibrium was reached.

[0061] By comparing the adsorption capacity of pollutants by products of various proportions, it was found that the optimal component content of ATP / CCS / SA-PEI aerogel in Example 1 was 0.6 g sodium alginate, 1.2 g CCS, 1 g ATP and 0.75 g PEI, which was the best component with the highest adsorption capacity.

[0062] The composite aerogel was prepared under the conditions of CCS dosage of 1.2g, SA dosage of 0.6g, ATP dosage of 1g, and PEI dosage of 0.75g. The static and dynamic adsorption effects of the composite gel on Cu(Ⅱ), MB and CR were tested as follows: Figure 3 As shown, the static adsorption capacity of aerogel for Cu(Ⅱ), MB and CR can reach up to 180.81, 176.89 and 279.31 mg / g, respectively, and the dynamic adsorption capacity can reach up to 228.24, 206 and 290.13 mg / g, respectively, indicating that aerogel has a good adsorption effect.

[0063] The changes in the aerogel element content before and after adsorption were tested by EDS, such as Figure 4 As shown in the figure, Cu(Ⅱ), MB and CR were successfully adsorbed, mainly by chemical complexation with the amino, hydroxyl and carboxyl groups on the surface of the aerogel. In addition, the higher pore structure can also adsorb Cu(Ⅱ), MB and CR through physical action.

[0064] The adsorption amount of Cu(Ⅱ), MB and CR by each raw material and aerogel in Example 1 was tested, and the results are shown in Table 2. In the adsorption experiment, 0.05g of ATP, CCS, SA, ATP / CCS / SA prepared in Example 1 and ATP / CCS / SA-PEI prepared in Example 1 were accurately weighed and introduced into a 50mL stoppered colorimetric tube containing Cu(Ⅱ) (300mg / L, pH=6), MB (300mg / L, pH=8) and CR (300mg / L, pH=8) solution. The colorimetric tube was sealed and the adsorption process was carried out in a fume hood at ambient temperature. 1.00mL of the solution was poured into a 50mL volumetric flask regularly and diluted to volume with water for analysis. Subsequently, the buffer solution was introduced into the solution together with the color developer. The absorbance value of Cu(II) ions was then measured at 450nm, the absorbance value of MB was measured at 664nm, and the absorbance value of CR was measured at 498nm until equilibrium was reached.

[0065] Table 2 Adsorption amount of Cu(Ⅱ), MB and CR by raw materials and products

[0066]

[0067]

[0068] As shown in Table 2, the pure raw materials are only rich in one adsorption group and have a certain adsorption effect. The products we prepared combine their respective advantages, so that the prepared aerogel is rich in adsorption groups such as hydroxyl (-OH), carboxyl (-COOH) and amino (-NH2), and the adsorption performance is effectively improved through hydrogen bond interaction, electrostatic interaction and coordination between them and pollutants.

[0069] Comparative Example 1

[0070] A preparation method of diatomite / carboxylated chitosan / sodium alginate-polyethyleneimine DE / CCS / SA-PEI aerogel:

[0071] First, 20 g of 6 wt% CCS aqueous solution was added dropwise to 20 g of 3 wt% SA aqueous solution and stirred vigorously at 1500 rpm for 1 h. Afterwards, 20 g of 5 wt% diatomaceous earth DE suspension was added dropwise to the above SA / CCS solution and stirred at 500 rpm for 2 h to obtain a uniformly mixed slurry of DE / CCS / SA mixture. Finally, 10 mL of PEI aqueous solution of different concentrations (2.5%, 5%, 7.5%, 10%, w / w) was added to the mixture and stirred vigorously at 1500 rpm for 30 min. Then, the mixture was poured into a plastic mold and freeze-dried at -60 °C, vacuum: 2 mbar, and freeze-dried for 24 h. The aerogel obtained from the first freeze-drying was immersed in a 10 wt% CaCl2 solution to allow SA and CCS to react with CaCl2. 2+ After that, the aerogel was removed after immersion for 4 h and thoroughly washed with distilled water to remove the incompletely cross-linked PEI and Ca 2+ The washed aerogel was then freeze-dried again to obtain DE / CCS / SA-PEI aerogel.

[0072] Comparative Example 2

[0073] A preparation method of bentonite / carboxylated chitosan / sodium alginate-polyethyleneimine MMT / CCS / SA-PEI aerogel:

[0074] First, 20g of 6wt% CCS aqueous solution was added dropwise to 20g of 3wt% SA aqueous solution and stirred vigorously at 1500rpm for 1h. Afterwards, 20g of 5wt% bentonite MMT suspension was added dropwise to the above SA / CCS solution and stirred at 500rpm for 2h to obtain a uniformly mixed slurry of MMT / CCS / SA mixture. Finally, 10ml of PEI aqueous solution of different concentrations (2.5%, 5%, 7.5%, 10%, w / w) was added to the mixture, stirred vigorously at 1500rpm for 30min, poured into a plastic mold, and freeze-dried at -60°C and vacuum: freeze-dried for 24h at 2mbar. The aerogel obtained from the first freeze-drying was immersed in a 10wt% CaCl2 solution to allow SA and CCS to react with CaCl2. 2+ After that, the aerogel was removed after immersion for 4 h and thoroughly washed with distilled water to remove the incompletely cross-linked PEI and Ca 2+ The washed aerogel was then freeze-dried again to obtain MMT / CCS / SA-PEI aerogel.

[0075] Figure 5These are SEM images of aerogels prepared in Comparative Examples 1 and 2, where a and b are SEM images of DE / CCS / SA-PEI; c and d are SEM images of MMT / CCS / SA-PEI. Although the two aerogels have layered structures, they have few pores and their surfaces are relatively smooth.

[0076] The aerogels of Comparative Example 1 and Comparative Example 2 were tested for adsorption in the same manner as in Example 1. The results are shown in FIG. Figure 6 And as shown in Table 3.

[0077] Figure 6 The adsorption curves of the aerogels prepared in Example 1 and Comparative Examples 1 and 2; Experimental conditions: the adsorption of Cu (pH=6, solution concentration: 300 mg / L, adsorbent mass: 50 mg), the adsorption of MB (pH=8, solution concentration: 300 mg / L, adsorbent mass: 50 mg), and the adsorption of CR (pH=8, solution concentration: 300 mg / L, adsorbent mass: 50 mg) were all carried out at room temperature. Figure 6 In the figure, a is the adsorption curve of Cu(Ⅱ) by DE / CCS / SA-PEI, MMT / CCS / SA-PEI and ATP / CCS / SA-PEI; b is the adsorption curve of MB by DE / CCS / SA-PEI, MMT / CCS / SA-PEI and ATP / CCS / SA-PEI; c is the adsorption curve of CR by DE / CCS / SA-PEI, MMT / CCS / SA-PEI and ATP / CCS / SA-PEI.

[0078] Table 3 Maximum adsorption data of Cu(Ⅱ), MB and CR by three composite aerogels

[0079]

[0080]

[0081] According to Table 3, the adsorption amount of the prepared ATP / CCS / SA-PEI is the highest, and the effect is much higher than the other two.

[0082] In addition, the present invention further explores the adsorption capacity of three clay materials for Cu(II), MB and CR, and the adsorption steps:

[0083] In the adsorption experiments, 0.05 g of DE, MMT, and ATP were accurately weighed and introduced into a 50 mL stoppered colorimetric tube containing Cu(II) (300 mg / L, pH = 6), MB (300 mg / L, pH = 8), and CR (300 mg / L, pH = 8) solutions. The colorimetric tube was sealed and the adsorption process was carried out in a fume hood at ambient temperature. 1.00 mL of the solution was periodically poured into a 50 mL volumetric flask and diluted to volume with water for analysis. Subsequently, a buffer solution was introduced into the solution together with the color developer. The absorbance values ​​of Cu(II) ions were then measured at 450 nm, the absorbance values ​​of MB were measured at 664 nm, and the absorbance values ​​of CR were measured at 498 nm until equilibrium was reached; the results are shown in Table 4.

[0084] Table 4 Adsorption of Cu(Ⅱ), MB and CR by three clay materials

[0085]

[0086] It can be seen from Table 4 that the adsorption of Cu(Ⅱ), MB and CR by ATP alone is not significantly better than that by DE and MMT, and some adsorption is even lower than that by DE and MMT. However, the adsorption of Cu(Ⅱ), MB and CR by aerogel ATP / CCS / SA-PEI prepared by the present invention is significantly better than that by DE / CCS / SA-PEI and MMT / CCS / SA-PEI. This shows that the present invention uses ATP to prepare aerogel materials, which synergizes with other materials to improve the adsorption of Cu(Ⅱ), MB and CR.

[0087] The SA selected in the present invention is a natural polysaccharide material, which contains abundant carboxyl functional groups as controllable modification sites, ATP is an inorganic clay material, has a porous nanostructure, shows strong adsorption, and has strong cation exchangeability, CCS and PEI polymer surfaces have abundant amino and hydroxyl groups, which can be used as ion adsorption sites, and PEI is used as a nucleation site and an ion crosslinker to promote material modification and crosslinking to form aerogel. As a dye and an ion adsorbent, the aerogel can be adsorbed by chemical chelation between functional groups and ions, and can also be physically adsorbed by a porous structure, thereby showing efficient adsorption performance. And the preparation method of the present invention is simple, and the aerogel ATP / CCS / SA-PEI has a uniform morphology and good thermodynamic stability, and can be recycled and reused after adsorption.

[0088] The description of the above embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. A method for preparing ATP / CCS / SA-PEI aerogel, characterized in that: The preparation method comprises the following steps: 1) adding carboxylated chitosan CCS solution dropwise to sodium alginate SA solution and stirring to obtain CCS / SA solution; 2) adding the attapulgite ATP suspension to the CCS / SA solution, stirring, and then adding the polyethyleneimine PEI solution, stirring to form a mixed solution; 3) pouring the mixed solution obtained in step 2) into a mold and freeze-drying it, soaking the obtained aerogel in a calcium chloride solution, then washing it with water; and then freeze-drying it to obtain ATP / CCS / SA-PEI aerogel.

2. The preparation method according to claim 1, characterized in that: In step 1), the stirring refers to stirring the reaction at room temperature for 1 hour at a stirring rate of 1500 rpm.

3. The preparation method according to claim 1 or 2, characterized in that: In step 1), the concentration of the carboxylated chitosan CCS solution is 6 wt %; the concentration of the sodium alginate SA solution is 3 wt %.

4. The preparation method according to claim 1 or 2, characterized in that: In step 2), the concentration of the attapulgite ATP suspension is 2.5-10wt%; the mass concentration of the polyethyleneimine PEI solution is 2.5-10wt%.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The weight ratio of carboxylated chitosan CCS in carboxylated chitosan CCS solution, sodium alginate in sodium alginate SA solution, attapulgite in attapulgite ATP suspension, and polyethyleneimine in polyethyleneimine PEI solution is 1.2:0.6:0.5-2:0.25-1; the preferred mass ratio is: 1.2:0.6: 1:0.75。 6. The preparation method according to claim 1, characterized in that: In step 2), the attapulgite ATP suspension is added to the CCS / SA solution, and the reaction time is 2 hours under stirring at room temperature; the polyethyleneimine PEI solution is added and stirred to form a mixed solution for 0.5 hours.

7. The preparation method according to claim 1, characterized in that: Step 3) freeze drying twice, both at -60°C for 48 hours.

8. An ATP / CCS / SA-PEI aerogel prepared by the preparation method according to any one of claims 1 to 7.

9. An application of the ATP / CCS / SA-PEI aerogel according to claim 8, characterized in that: Used for dye pollutant adsorption.

10. An application of the ATP / CCS / SA-PEI aerogel according to claim 8, characterized in that: Used for heavy metal ion adsorption.

Citation Information

Patent Citations

  • Sewage treating agent for heavy metal pollution

    CN108439525A

Cited By

  • Preparation method of self-adaptive anti-electromagnetic interference composite material

    CN120271889A